2013
DOI: 10.1101/gr.160465.113
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for detecting uniparental disomy from trio genotypes identifies a significant excess in children with developmental disorders

Abstract: Exome sequencing of parent-offspring trios is a popular strategy for identifying causative genetic variants in children with rare diseases. This method owes its strength to the leveraging of inheritance information, which facilitates de novo variant calling, inference of compound heterozygosity, and the identification of inheritance anomalies. Uniparental disomy describes the inheritance of a homologous chromosome pair from only one parent. This aberration is important to detect in genetic disease studies beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 59 publications
1
73
2
Order By: Relevance
“…In addition, the higher cost of SNP array technology, as compared with array CGH, may limit the use of the SNP array in some centers as a first-line genetic test in children with developmental delay. Although UPD seems to be quite rare in the general population and is estimated at one in 3500 live births, a recent study showed a significant 25 × enrichment of UPD in children with developmental disorders (Robinson, 2000;King et al, 2014). The possibility of UPD may therefore be an argument for including SNP arrays in the genetic workup of children with developmental delay, especially those with complex phenotypes.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the higher cost of SNP array technology, as compared with array CGH, may limit the use of the SNP array in some centers as a first-line genetic test in children with developmental delay. Although UPD seems to be quite rare in the general population and is estimated at one in 3500 live births, a recent study showed a significant 25 × enrichment of UPD in children with developmental disorders (Robinson, 2000;King et al, 2014). The possibility of UPD may therefore be an argument for including SNP arrays in the genetic workup of children with developmental delay, especially those with complex phenotypes.…”
Section: Discussionmentioning
confidence: 94%
“…UPD was called using UPDio 14 . CNV calls (Supplemental Materials and Methods), were masked and not considered by UPDio.…”
Section: Methodsmentioning
confidence: 99%
“…18 Array comparative genomic hybridization was performed with a custom, exome-focused, two million probe Agilent aCGH array; CNVs were called via CNsolidate, a Sanger Centre in-house algorithm that integrates 12 change-point detection algorithms (T. Fitzpatrick, P. Vijayarangakannan, N. Carter, M.E.H., data not shown); uniparental disomy was detected with UPDio. 19 To confirm triplication and AOH independently, samples were run on two different array platforms. For instance, BAB4539 plus parental samples were run on an Affymetrix CytoScan SNP array and samples BAB3922, BAB3923, and BAB3924 plus parental samples were analyzed with A B C Figure 1.…”
Section: Determining Triplication Size and Absence Of Heterozygosity mentioning
confidence: 99%